Recombinant COVID-19 vaccine based on recombinant RBD/Nucleoprotein and saponin adjuvant induces long-lasting neutralizing antibodies and cellular immunity - Ghaemi, Amir; Roshani Asl, Parisa; Zargaran, Hedieh; Ahmadi, Delaram; Hashimi, Asim Ali; Abdolalipour, Elahe; Bathaeian, Sahar; Miri, Seyed Mohammad (Frontiers in Immunology, 2022)
SARS-CoV-2 has caused a global pandemic, infecting millions of people. An effective preventive vaccine against this virus is urgently needed. Here, we designed and developed a novel formulated recombinant receptor-binding domain (RBD) nucleocapsid (N) recombinant vaccine candidates. The RBD and N were separately expressed in E. coli and purified using column chromatography. The female Balb/c mice were immunized subcutaneously with the combination of purified RBD and N alone or formulated with Saponin adjuvant in two-week interval in three doses. Neutralization antibody (Nabs) titers against the SARS-CoV-2 were detected by a Surrogate Virus Neutralization (sVNT) Test. Also, total IgG and IgG1 and IgG2a isotypes, and the balance of cytokines in the spleen IFN-γ, Granzyme B, IL-4, and IL-12) were measured by ELISA. The percentages of CD4+ and CD8+ T cells were quantified by flow cytometry. The lymphoproliferative activity of restimulated spleen cells was also determined. The findings showed that the combination of RBD and N proteins formulated with Saponin significantly promoted specific total IgG and neutralization antibodies, elicited robust specific lymphoproliferative and T cell response responses. Moreover, marked increase in CD4+ and CD8+ T cells were observed in the adjuvanted RBD and N vaccine group compared with other groups. The results suggest that the formulations are able to elicit a specific long-lasting mixed Th1/Th2 balanced immune response. Our data indicate the significance of the Saponin- adjuvanted RBD-N vaccine in the design of SARS-CoV-2 vaccines and provide a rationale for the development of a protective long-lasting and strong vaccine.